Understanding Terminological Systems I: Terminology and Typology - de Keizer, N. F.; Abu-Hanna, A.; Zwetsloot-Schonk, J. H. M. (Methods of Information in Medicine, 2000)
Terminological systems are an important research issue within the field of medical informatics. For precise understanding of existing terminological systems a referential framework is needed that provides a uniform terminology and typology of terminological systems themselves. In this article a uniform terminology is described by putting relevant fundamental notions and definitions used by standard organizations such as CEN and ISO into perspective, and interrelating them to arrive at a useful typology of terminological systems. This typology is illustrated by applying it to five well-known existing terminological systems.
Keywords: Terminology; Typology; Terminological Systems; Standards